The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.macromol.1c01820
|View full text |Cite
|
Sign up to set email alerts
|

Ion Specific, Thin Film Confinement Effects on Conductivity in Polymerized Ionic Liquids

Abstract: Acrylate-based polymerized ionic liquids (PILs) with ammonium (Am) or imidazolium (Im) cations and tetrafluoroborate (BF 4 ) or bis(trifluoromethanesulfonyl)imide (TFSI) anions were synthesized and spin coated onto gold interdigitated electrodes on silica to investigate nanoconfinement effects on ion transport. The film thickness ranged from 23 to 313 nm. A significant reduction of the inplane conductivity was observed in some PIL thin films with thickness below 100 nm. Specifically, Am BF 4 PIL showed the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Understanding the structural characteristics of polymer thin films is critical to numerous emerging technologies. , For example, self-assembly of block copolymer ( e.g. , layer and cylinder) in thin films is essential to using these materials for nanolithography because the phase behavior can be significantly perturbed relative to the bulk behavior due to interfacial and confinement effects. Also, conjugated polymers are widely studied in thin-film geometries because the alkyl chain crystallinity and π–π stacked assemblies impact the electron transport properties, , which are valuable for transistors, light-emitting diodes, and photovoltaics. Similarly, structure–property relationships of ion-containing polymer thin films have received significant interest for their ion transport abilities. The perfluorinated sulfonic acid polymers ( e.g. , Nafion) are among the most extensively studied ionomers for their applications in the catalyst layer of fuel cells and solar-fuel generators. , Specifically, the studies of Nafion have indicated that producing aligned morphologies of phase-separated sulfonic acid aggregates in a thin film can improve the proton transport properties or catalytic performance. , …”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Understanding the structural characteristics of polymer thin films is critical to numerous emerging technologies. , For example, self-assembly of block copolymer ( e.g. , layer and cylinder) in thin films is essential to using these materials for nanolithography because the phase behavior can be significantly perturbed relative to the bulk behavior due to interfacial and confinement effects. Also, conjugated polymers are widely studied in thin-film geometries because the alkyl chain crystallinity and π–π stacked assemblies impact the electron transport properties, , which are valuable for transistors, light-emitting diodes, and photovoltaics. Similarly, structure–property relationships of ion-containing polymer thin films have received significant interest for their ion transport abilities. The perfluorinated sulfonic acid polymers ( e.g. , Nafion) are among the most extensively studied ionomers for their applications in the catalyst layer of fuel cells and solar-fuel generators. , Specifically, the studies of Nafion have indicated that producing aligned morphologies of phase-separated sulfonic acid aggregates in a thin film can improve the proton transport properties or catalytic performance. , …”
Section: Introductionmentioning
confidence: 76%
“… 8 11 Similarly, structure–property relationships of ion-containing polymer thin films have received significant interest for their ion transport abilities. 12 15 The perfluorinated sulfonic acid polymers ( e.g. , Nafion) are among the most extensively studied ionomers for their applications in the catalyst layer of fuel cells and solar-fuel generators.…”
Section: Introductionmentioning
confidence: 99%
“…The glass transition temperature, T g , is a key characteristic of polymer materials because many physical and mechanical properties change markedly when a polymer undergoes a glass transition from a rubbery state to a glassy state or vice versa. , For polymer films confined at the nanoscale, perturbations originating at the polymer/free surface and the polymer/solid interfaces often result in deviations of the measured T g from the bulk T g . Such nanoconfinement behavior is important because it can affect the commercial application of ultrathin polymer films and may aid in understanding the underlying mechanisms of glass transition behavior, which has been a long-standing, unresolved challenge. Indeed, the T g -confinement behavior of polymers has been the subject of intense research since 1994 when Keddie et al , first reported that, relative to bulk T g , the T g s of polystyrene (PS) and poly­(methyl methacrylate) ultrathin films supported on silicon decrease and increase, respectively, with decreasing nanoscale thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Conductivity in specific thin-film systems is influenced by solvation-segmental dynamics of ethylene-oxide side chains [23]. The same study that drew connections between substrate properties also concluded that conductivity is affected by confinement [17].…”
Section: Filmsmentioning
confidence: 91%
“…In some cases, the manufacturing of film substrates requires glass transition temperatures greater than the annealing temperature ≈ 150 • C [12]. Moreover, properties of the thin-film substrate, such as the conductivity, are also dominated by dynamics [17].…”
Section: Filmsmentioning
confidence: 99%